Loss of OsEAF6, a Subunit of the Histone Acetyltransferase Complex, Causes Hybrid Breakdown in Intersubspecific Rice Crosses - Kubo, Takahiko; Yoshimura, Atsushi; Kurata, Nori (Frontiers in Plant Science, 2022)
Gene duplication plays an important role in genetic diversification, adaptive evolution, and speciation. Understanding the mechanisms and effects of postzygotic isolation genes is important for further studies of speciation and crop breeding. The duplicate recessive genes hwe1 and hwe2 cause hybrid breakdown, characterized by poor vegetative growth and reproductive dysgenesis in intersubspecific crosses between Oryza sativa ssp. indica and japonica. Using a map-based cloning strategy, we found that HWE1 and HWE2 encode the Esa1-associated factor 6 (EAF6) protein, a component of histone acetyltransferase complexes. The indica hwe1 and japonica hwe2 alleles lacked functional EAF6, demonstrating that the double recessive homozygote causes hybrid breakdown. Morphological and physiological observations showed that weak plants with double recessive homozygotes had serious morphological defects with a wide range of effects on development and organs, leading to leaves with reduced chlorophyll content, flower and pistil malformation, and anomalies of gametogenesis. These findings suggest that EAF6 plays a pivotal role in the transcriptional regulation of essential genes during the vegetative and reproductive development of rice.